ENT530 : Food Factory Enterprise / Nurul Farayani Kamarulzaman ... [et al.] - Kamarulzaman, Nurul Faryani; Ahmad, Aida Fatin; Shaari, Shafiqah; Mohd Jainuri, Nurhayatie (2019)
Food Factory Enterprise is a partnership business company. W.e. registered on 1st January 209^and start our business on 31st January 2030. Its name, Food Factory Enterprise is due to it sounds friendly and universal to our target market. We also want to pay tribute to our partner's late father who once a factory worker that has been our inspiration to open the restaurant. Our calling is to share the finest pizza and pasta with Malaysian palates. For fine pizza and pasta, and all the great ingredients that go into them, our restaurant is the best place to go.